1991
DOI: 10.1111/j.1755-3768.1991.tb02705.x
|View full text |Cite
|
Sign up to set email alerts
|

High myopia with cone dysfunction

Abstract: All 3 children, 2 boys and 1 girl (the probands), in a family had high myopia and subnormal visual acuities. The boys had high myopia in both eyes, the girl had high myopia in 1 eye and low myopia in the other eye. Both of the boys had a protanomalous colour vision defect. The colour vision testing of the high myopic eye of the girl was not successful, the other eye had normal colour vision. In the electroretinogram examination, both cone and rod responses were decreased in 2 of the children. In the family stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Subsequent studies demonstrated a high prevalence of myopia in PDE6C ACHM (myopia > 6D in 63% of patients) 14 , and increased susceptibility to form-deprivation myopia in a mouse model of GNAT2 ACHM 15 . Increased prevalence of high myopia has also been reported in other cone dysfunction retinopathies 16 19 . Contrary to these reports, other studies report a high prevalence of hyperopia 20 or a combination of both 5 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 84%
“…Subsequent studies demonstrated a high prevalence of myopia in PDE6C ACHM (myopia > 6D in 63% of patients) 14 , and increased susceptibility to form-deprivation myopia in a mouse model of GNAT2 ACHM 15 . Increased prevalence of high myopia has also been reported in other cone dysfunction retinopathies 16 19 . Contrary to these reports, other studies report a high prevalence of hyperopia 20 or a combination of both 5 , 21 , 22 .…”
Section: Introductionmentioning
confidence: 84%